Exchange Rate Expectations : Survey of Survey Studies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This paper presents a brief survey of the empirical literature on survey-based exchange rate expectations. The literature in general supports the presence of a non-zero risk premium and rejects the hypothesis of rational expectations. The crucial result is that, while short-run expectations tend to move away from some long-run 'normal' values, long-run expectations tend to regress toward them. If this nature of short-run expectations increases the volatility of exchange rate movements, there may be a basis for some official measure to minimize short-run exchange rate movements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet